2007
DOI: 10.1179/136485907x154511
|View full text |Cite
|
Sign up to set email alerts
|

Loiasis — a neglected and under-estimated affliction: endemicity, morbidity and perceptions in eastern Cameroon

Abstract: Loiasis is a neglected disease that may have great social and economic impact in some endemic areas. This study was designed to update the geographical distribution of loiasis and assess the frequency and perceptions of the clinical signs of the disease in the Eastern province of Cameroon. The investigation covered 32 villages and involved 4146 respondents. Human infection with Loa loa was endemic in all the study villages but the prevalence of microfilaraemia generally decreased from south to north. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…The RAPLOA method is based on the history of clinical manifestations and largely depends on the appreciation of the eye worm phenomenon by the members of a community. The results of our validation study confirmed previous observations that the experience of eye worm migration is well known by members of endemic communities irrespective of their cultures and dialects [10,23,24] and that they have descriptive local names for the phenomenon. The subconjunctival migration of adult L. loa is a spectacular phenomenon in endemic communities, which are often located far from any health facility.…”
Section: Discussionsupporting
confidence: 88%
“…The RAPLOA method is based on the history of clinical manifestations and largely depends on the appreciation of the eye worm phenomenon by the members of a community. The results of our validation study confirmed previous observations that the experience of eye worm migration is well known by members of endemic communities irrespective of their cultures and dialects [10,23,24] and that they have descriptive local names for the phenomenon. The subconjunctival migration of adult L. loa is a spectacular phenomenon in endemic communities, which are often located far from any health facility.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with a previous report from endemic areas. 15 Although Calabar swellings typically appear on extremities, 3,13 some patients experienced swellings on other parts of the body: swellings on the eyelid were seen more frequently than that on the upper arms in this series.…”
Section: Discussionmentioning
confidence: 57%
“…Although the overwhelming majority of L. loainfected individuals are clinically asymptomatic, Calabar swelling (transient, localized angioedema), and the subconjunctival migration of an adult worm ("eyeworm") are the most common clinical manifestations (3)(4)(5). Rarely, nephropathy, cardiomyopathy, retinopathy, neuropsychiatric complications, and encephalopathy (6)(7)(8)(9)(10)(11)(12) can occur as a consequence of chronic infection.…”
mentioning
confidence: 99%